Correlation - Samia Aleem; Qazi Masood; Iffat Hassan (Wolters Kluwer Medknow Publications, 2015)
Background: Chronic urticaria (CU) is a multifactorial disease, however, in a majority of patients, it is not possible to ascribe a specific aetiology, which is termed 'idiopathic'. Although autoimmunity has been implicated as a principal cause in 30-50% of these idiopathic cases, activation of coagulatory and inflammatory cascades has gained attention in last few years. Aims: To evaluate levels of mean platelet volume, an indicator of platelet activity, in patients with chronic urticaria and determine its correlation with its severity. Methods: Mean platelet volume levels were assessed in 194 patients with chronic urticaria and were compared with equal number of age and sex matched controls. Its levels were also correlated with the severity of urticaria and results of autologous serum skin test. Result: Mean platelet volume (MPV) levels were found to be higher in patients with ASST positive chronic urticaria compared to patients with ASST negative chronic urticaria and controls. MPV levels also showed a positive correlation with the severity of chronic urticaria. Conclusion: As platelets secrete and express a number of crucial mediators of coagulation and inflammation, coagulation and inflammatory cascades may play a positive role in chronic urticaria, paving the way for better understanding of pathogenesis and introduction of newer drugs.